PERANCANGAN SISTEM PENJUALAN ALAT JAHIT BERBASIS WEB DI TOKO MAKASSAR TIGA PUTRI 2 - Galih P, Ramadhan; Anggi S, Fajar; Padrisi, Zaman; Haryono, Wasis (Journal Information & Computer, 2023)
At this time the development of information has grown very rapidly, therefore there are also many companies or agencies that use information systems to improve their business in order to compete with the offline and online trading world in order to make sales easily and can interact with customers and make it easier for customers to see or choose in advance what they want to find or use, the company must make improvements in business or how to sell their products. The way to improve a company's business is to build a good information system. And the requirement to build a good information system is the speed and accuracy to obtain the information needed by the customer in order to make it easier for the customer to find their needs. Based on the description above, the formulation of the problem in this KP is: A. How is the web-based goods data collection system needed by the customer at MAKASSAR TIGA PUTRI 2 SHOP 2 B. How to make an attractive and easily accessible sales web design for customers at MAKASSAR TIGA PUTRI 2 SHOP - Sales are still on a regular basis manual and offline - Customers are still having trouble finding the name of the goods - Sellers have difficulty controlling the stock of goods that exist or do not exist In the design of this application aims to develop a sales system from this company, which can increase the company's sales. With this application, it is also easier for customers to shop for school equipment needs online, thus saving more time in shopping. This application also needs maintenance every month so that this application runs better. However, this application is designed as well as possible with valid data according to its original state to cover the shortcomings of the application. The application is also designed so that customers have confidence in the convenience offered by the applicationKeywords: Designing a web-based sewing tool sales system using the prototype method